An observational study demonstrating the adherence and ease of use of the injector device, RebiSmart® - Vališ, Martin; Šarláková, Jana; Halúsková, Simona; Klímová, Blanka; Potužník, Pavel; Peterka, Marek; Kuča, Kamil; Štourač, Pavel; Mareš, Jan; Pavelek, Zbyšek (Expert opinion on drug delivery, 2020)
Background: Adherence to Multiple Sclerosis (MS) treatment is considered one of the crucial factors for ensuring optimal clinical outcomes. Research has shown that the use of self-injector devices improves patient compliance with treatment. Therefore, the main purpose of this study is to evaluate the ease of use of RebiSmart® 2.0 in clinically isolated syndrome/relapsing-remitting MS patients during 12 months treatment period.Methods: A total number of 290 subjects entered into data collection; 249 (86%) of them completed the whole 12 months study period. The primary endpoints and the secondary endpoints were assessed by the User Study Questionnaire. Adherence data were retrieved from RebiSmart® 2.0 (Menu - Dose History) on the respective patient's visit. Outcome measures also included Expanded Disability Status Score, Kurtzke Functional Systems, and Modified Social Support Survey, Modified Social Support Survey-5.Results: This study demonstrated a very high proportion (>95%) of patients with a positive rating of the overall ease of use and the overall convenience of RebiSmart®. The proportion of patients with a positive rating of the ease of use by individual domains and the functions of RebiSmart® were also high (>80%).Conclusion: The findings demonstrate a very good perception of the usability of the device by patients overall and in its individual functions.
Keywords: Young Adult; Male; mladý dospělý; adherence k farmakoterapii; Adolescent; Adult; dospělí; relabující-remitující roztroušená skleróza; mužské pohlaví; Multiple Sclerosis, Relapsing-Remitting; průzkumy a dotazníky; mladiství; Medication Adherence; injekce; lidé; ženské pohlaví; interferon beta 1a; Injections; Humans; Interferon beta-1a; Female; Surveys and Questionnaires; lidé středního věku; Middle Aged